The effect of sintered aid CuO-Bi2O3 on microwave dielectric properties of (Pb0.45Ca0.55)[(Fe0.5Nb0.5)(0.9)Sn-0.1]O-3 ceramics - Ha, JY; Choi, JW; Kim, HJ; Yoon, SJ; Yoon, KH (ELSEVIER SCIENCE SA, 2003)
The microwave dielectric properties of (Pb0.45Ca0.55)[(Fe0.5Nb0.5)(0.9)Sn-0.1]O-3 (PCFNS) with x wt.% CuO-y wt.% Bi2O3 have been investigated. The PCFNS ceramics was sintered at 1165 degreesC. In order to decrease the sintering temperature for using as a low-temperature co-firing ceramics (LTCC), CuO-Bi2O3 were added in the PCFNS. When 0.1 wt.% CuO-y wt.% Bi2O3 doped PCFNS was sintered at 1000 degreesC, density and dielectric constant (epsilon(r)) were increased as increasing the contents y of Bi2O3. When CuO content of was fixed as 0.2 wt.%, density and dielectric constant (epsilon(r)) were decreased with an increase of Bi2O3 content and quality factor value (Qf(0)) was decreased as increasing Bi2O3 content having no relation with CuO content and temperature coefficient of resonant frequency (tau(f)) was decreased as increasing Bi2O3 content. When CuO of 0.2 wt.% and Bi2O3 of 0.4 wt.% were added, microwave dielectric composition having good properties were obtained and the properties were epsilon(r) of 86, Qf(0) of 4340 GHz, tau(f) of 8 ppm degreesC(-1), and sintering temperature of 1000 degreesC for this composition. The relationship between the microstructure and microwave dielectric properties was studied by powder X-ray diffraction (XRD), scanning electron microscope (SEM). (C) 2002 Elsevier Science B.V All rights reserved.
Keywords: GLASS ADDITIONS; BA(ZN1/3TA2/3)O-3; (ZR,SN)TIO4